Crystal Growth and Spectroscopy of Yb2+-Doped CsI Single Crystal - Sofich, Dmitriy; Myasnikova, Alexandra; Bogdanov, Alexander; Pankratova, Viktorija; Pankratov, Vldimir; Kaneva, Ekaterina; Shendrik, Roman (MDPI, 2024)
The single crystals of CsI-Yb2+ were grown, and their spectroscopic studies were conducted. The observed luminescence in CsI-Yb2+ is due to 5d–4f transitions in Yb2+ ions. Using time-resolved spectroscopy, spin-allowed and spin-forbidden radiative transitions of ytterbium ions at room temperature were found. The excitation spectra of Yb2+ luminescence bands were obtained in the range of 3–45 eV. The mechanism of charge compensation of Yb2+ ions in a CsI crystal was also studied, the spectrum of the thermally stimulated depolarization current was measured, and the activation energies of the two observed peaks were calculated. These peaks belong to impurity–vacancy complexes in two different positions. The charge compensation of Yb2+ occurs via cation vacancies in the nearest-neighbor and next-nearest-neighbor positions. The Yb2+ ions are promising dopants for CsI scintillators and X-ray phosphors in combination with SiPM photodetectors. © 2024 by the authors. --//-- This is an open-access article Sofich, D.; Myasnikova, A.; Bogdanov, A.; Pankratova, V.; Pankratov, V.; Kaneva, E.; Shendrik, R. Crystal Growth and Spectroscopy of Yb2+-Doped CsI Single Crystal. Crystals 2024, 14, 500. https://doi.org/10.3390/cryst14060500 published under the CC BY 4.0 licence.
The authors are grateful to Kirill Chernenko for helping with the measurements at the MAX IV synchrotron facility. The geometry optimization was supported by the Russian academy of Science basic program (0284-2021-0004).The work of Vladimir Pankratov is supported by the LZP grant (2022/1-0611), while Viktorija Pankratova acknowledges the LZP grant (2023/1-0453). The Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union\u2019s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2. We acknowledge the MAX IV Laboratory for time on the FinEstBeAMS Beamline under Proposal 20211074. Research conducted at MAX IV, a Swedish national user facility, is supported by the Swedish Research council under contract 2018-07152, the Swedish Governmental Agency for Innovation Systems under contract 2018-04969, and Formas under contract 2019-02496.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; cesium iodide; Czochralski method; luminescence; single crystal; ytterbium